PENGARUH PELATIHAN, EFIKASI DIRI DAN KETERIKATAN KARYAWAN TERHADAP KINERJA KARYAWAN (Studi pada Patra Semarang Hotel & Convention) - Ardanti, Desti Marina; Rahardja, Edy (Diponegoro Journal of Management, 2017)
This study aims to investigate the effect of training, self-efficacy, and employee engagement on employee performance at Patra Semarang Hotel & Convention. The techniques of data analysis that used in this research were validity, reliability, classic assumption test, t test, F test, the coefficient of determination and multiple linear regression analysis to determine the effect of that three independent variables. Respondents in this study were 62 respondents. The result indicates that there are : training has positive and significant impact on employee performance, self-efficacy has positive and significant impact on employee performance, and employee engagement has positive and significant impact on employee performance. Based on the result of the F test is known that independent variables (training, self-efficacy, and employee engagement) has simultaneous and significant impact on employee performance. Independent variables that have been mentioned can explain the dependent variable by 58,9% while the remaining 41,1% can be explained by other variables. The result of this study are expected to help Patra Semarang Hotel & Convention to repair and make improvements in training, self-efficacy, and employee engagement in order to make employee performance much better.